Polycystic Ovarian Syndrome (PCOS): A Brief Overview on Pathogenesis, Main Signaling Pathways, and Recent Studies Performed on Letrozoleinduced PCOS in Rodents - Abduljabbar, Hana N.; Jamal, Maha H.; Esmat, Ahmed (Current Pharmaceutical Biotechnology, 2026)
Polycystic ovarian syndrome (PCOS) is a female endocrine and reproductive disease. The exact etiology remains unknown. There are several associated factors involved in the pathogenesis of PCOS, such as hyperandrogenism, insulin resistance, obesity, inflammation, oxidative stress, genetic, epigenetic, and environmental factors. However, the main diagnostic criteria involve at least two out of three symptoms, which are hyperandrogenism, polycystic ovaries, and menstrual cycle dysregulation. The treatment of the multiple symptoms of PCOS is still a medical challenge. Different molecular pathways have been studied in PCOS, such as PI3K-AKT, MAPK, NF-κB, and Keap-1-Nrf2 pathways, to visualize different mechanisms of action of this disease. In this regard, this review highlights the main signaling pathways involved in PCOS, as well as their associated studies retrieved from PubMed and Web of Science databases. In addition, several therapeutic approaches and targets that were tested on letrozole-induced PCOS in rodents were summarized and retrieved from the same databases over the past five years. For example, resveratrol, patuletin, adropin, mogroside V, Lepidium sativum seed extract, ascorbic acid, alendronate, probiotics, and mesenchymal stem cells, as well as lifestyle modifications, were shown to have positive effects in the management of PCOS. In conclusion, different approaches have been studied as potential treatments for PCOS according to different disease pathogeneses, molecular pathways, and associated symptoms, showing promising results that might be included in the PCOS therapeutic plan in the future.
Keywords: PI3K-AKT